The complete mitochondrial genome of Alphitobius diaperinus Panzer, 1797 (Coleoptera: Tenebrionidae). Issue 3 (2nd July 2020) - Hong, Ki-Jeong; Ki, Woong; Park, Doo-Sang; Yang, Byung-Kun; Lee, Hyobin; Park, Jongsun; Lee, Wonhoon
Abstract: Alphitobius diaperinus Panzer, 1797 is a major pest in poultry production and easily observed in poultry litter. We have determined mitochondrial genome of A. diaperinus collected in Chungcheongbuk-do, Republic of Korea. The circular mitogenome of A. diaperinus is 15, 511 bp long which is longer than that of Z. atratus but shorter than that of T. obscurus . It includes 13 protein-coding genes, two ribosomal RNA genes, and 22 transfer RNAs. The base composition was AT-biased (72.4%). Phylogenetic tree displays that tribe Alphitobiini is clustered with tribes Helopini and Diaperini with enough supportive values of three phylogenetic trees.